In-plane and single blade loads measurement setups for propeller performance assessment during free running and captive model tests. (1st December 2020) - Ortolani, Fabrizio; Dubbioso, Giulio
Abstract: During ship actual operative condition, the inflow experienced by the propeller is different from the one adopted during design phase: moderate, tight or emergency manoeuvres and heavy sea are some of the conditions that could occur, which alter the flow to the propeller. The resulting inflow gives rise to a complex system of loads developed by the blades and the propeller, which can cause failures and damages. Moreover, these loads have a direct impact on the manoeuvring ability of the ship, because act to stabilize the ship. The quantification of these loads and the assessment of their origin with ship dynamics and wake is pivotal to optimize the propulsive performance of the ship, mitigate their undesirable effects and, ultimately, achieve a successful design. In order to move further step with respect to standard monitoring of propeller performance in model testing and obtain a more complete set of information for the validation of numerical solvers, two novel experimental setups that were implemented and successfully tested on two ship models, are described in this paper. The first one is tasked for the measurements of the in-plane loads developed by the propeller, while by the second one is devoted to measure the complete set of loads generated by a single blade. Highlights: Development and application of a novel setup for propeller in-plane (i.e. bearing) loads and single blade loads measurements. Analysis in operative condition. Phenomenological description of the generation of blade loads. Asymmetric behavior for internal and external propellers of twin screw configuration.